2015
DOI: 10.1097/jom.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Occupation Is Related to Weight and Lifestyle Factors Among Employees at Worksites Involved in a Weight Gain Prevention Study

Abstract: Objective To examine the relationship between job type, weight status and lifestyle factors that are potential contributors to obesity including, diet, physical activity and perceived stress among employees enrolled in the Working on Wellness (WOW) project. Methods Randomly selected employees at 24 worksites completed a baseline survey (n=1700); some also an in-person survey and anthropometric measures (n=1568). Employees were classified by US Labor standards as: white collar (n=1297), blue collar (n=303), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Univariate analysis of our study shows that increased age, business/service persons, married people and individuals with more number of children are significantly likely to have multi-morbidity ( P < 0.05). Other studies on obesity also suggest increased age,[14] married people,[18] service holders[1920] and having more children[21] increases the risk for obesity and its related complications. However, no significant association of obesity with occupation was found in other study.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analysis of our study shows that increased age, business/service persons, married people and individuals with more number of children are significantly likely to have multi-morbidity ( P < 0.05). Other studies on obesity also suggest increased age,[14] married people,[18] service holders[1920] and having more children[21] increases the risk for obesity and its related complications. However, no significant association of obesity with occupation was found in other study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported higher rates of physical inactivity and obesity among white-collar workers, particularly female workers, than those in other occupations [39, 40]. Furthermore, physical inactivity during working hours negatively affects the health of white-collar workers [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moderate or strong PA inhibits the development of atherosclerosis and reduces total mortality by 20%–25%,27 which has been attributed to a range of effects such as reducing body weight, improving glucose tolerance28 or lipid profile. Blue-collar workers usually report high PA as a consequence of work conditions 29. The relationship observed between unemployment and low PA may be connected with higher susceptibility for cardiovascular diseases 30…”
Section: Introductionmentioning
confidence: 99%